'You-on-a-chip' for precision medicine. Issue 2 (4th March 2018) - Low, Lucie A.; Tagle, Danilo A.
ABSTRACT: Introduction : This forward-thinking review will introduce microphysiological systems (MPS), also known as organs-on-chips or tissue chips and their potential utility in personalized medicine. The authors will explain how this technology could push precision medicine efforts forward, using scenarios of current and projected use of MPS in different disease and treatment scenarios. Areas covered : The research discussed will include highlights of the last half decade of MPS development, with background information on microphysiological systems including within the context of precision medicine. This review will cite examples on cancer, neurological disorders and rare disease scenarios where MPS could be integrated into the decision-making process for physicians and healthcare providers. Expert commentary : This review will discuss how microphysiological systems could be used in a variety of situations for medical diagnostics, understanding disease mechanisms, and development of therapeutic treatment plans. A useful place in precision medicine efforts exists for MPS to help eliminate some of the 'guesswork' in standard therapeutic recommendations, and to inform future treatment regimens for subgroups of individuals based on the systems biology and -omics-based readouts these platforms can produce.